Body mass index a better predictor of insulin resistance than waist circumference in normoglycemics - B.L. Preethi; K.M. Prasannakumar; Vijay Culmalgae (Al Ameen Medical College, 2015)
Background: Body Mass Index (BMI) is the most common method of measuring obesity. Many studies have reported that waist circumference is a stronger predictor of insulin resistance in non-type 2 diabetes. The objective of the study was to investigate whether waist circumference (WC) or body mass index (BMI) is a better predictor insulin resistance. Method: 79 normal young adult volunteers in the age range of 18 to 25 years were enrolled for the Study. All subjects underwent a detailed general physical examination including Blood Pressure, body weight, height, hip & waist circumference. BMI (Body Mass Index), waist and hip circumference & waist hip ratio calculated. 2hr OGTT with serum Insulin was performed and Insulin resistance calculated. Result: Simple clinical measures of obesity like height, weight, waist circumference, hip circumference and their indexes like BMI (body mass index), WHR (waist hip ratio) were evaluated and correlated with the measures of Insulin resistance (IR) and insulin sensitivity. BMI was found to significantly correlate with most of the IR parameters and there was a trend towards significance with weight. Waist circumference did not correlate significantly with IR parameters. Conclusion: Body Mass Index (BMI) is a useful tool in evaluating obesity in normoglycemic subjects. BMI is a better predictor of Insulin Resistance and risk stratification than waist circumference.